Perceived social support and psychological well-being of international students: the mediating effects of resiliency and spirituality - Li, Yue Qi; Roslan, Samsilah; Zaremohzzabieh, Zeinab (UiTM Press, 2021)
International students are a significant resource for many host countries because they increase cultural diversity within the community, offer talent and innovation to universities, and make notable economic contributions. Many studies, however, have shown that international students have lower psychological well-being. Thus, this study aimed to evaluate the associations between psychological well-being as a dependent variable and perceived social support as an independent variable, and test the mediating roles of resiliency and spirituality in the link between perceived social support and psychological well-being. This is a cross sectional study with a random sampling method. A total of 300 Chinese international students in Universiti Putra Malaysia (UPM) participated in this study and completed four questionnaires, namely the Perceived Social Support scale, Psychological Well-being scale, the Spiritual Values scale, and Connor-Davidson Resilience scale. The results from PLS-SEM showed that greater levels of social support are associated with greater levels of psychological well-being. Resiliency and spirituality partially mediated the relationship between social support and psychological well-being. The findings of this study not only revealed an association between perceived social support and psychological well-being among Chinese international students in Malaysia but also expanded our knowledge of the mediating roles of resilience and spirituality in the relationship.